Functional bottlenecks for generation of HIV-1 intersubtype Env recombinants - Bagaya, Bernard S. (Retrovirology, 2015)
BACKGROUND: Intersubtype recombination is a powerful driving force for HIV evolution, impacting both HIV-1 diversity within an infected individual and within the global epidemic. This study examines if viral protein function/fitness is the major constraint shaping selection of recombination hotspots in replication-competent HIV-1 progeny. A better understanding of the interplay between viral protein structure-function and recombination may provide insights into both vaccine design and drug development. RESULTS: In vitro HIV-1 dual infections were used to recombine subtypes A and D isolates and examine breakpoints in the Env glycoproteins. The entire env genes of 21 A/D recombinants with breakpoints in gp120 were non-functional when cloned into the laboratory strain, NL4-3. Likewise, cloning of A/D gp120 coding regions also produced dead viruses with non-functional Envs. 4/9 replication-competent viruses with functional Env’s were obtained when just the V1-V5 regions of these same A/D recombinants (i.e. same A/D breakpoints as above) were cloned into NL4-3. CONCLUSION: These findings on functional A/D Env recombinants combined with structural models of Env suggest a conserved interplay between the C1 domain with C5 domain of gp120 and extracellular domain of gp41. Models also reveal a co-evolution within C1, C5, and ecto-gp41 domains which might explain the paucity of intersubtype recombination in the gp120 V1-V5 regions, despite their hypervariability. At least HIV-1 A/D intersubtype recombination in gp120 may result in a C1 from one subtype incompatible with a C5/gp41 from another subtype.